(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Ocean waves are a reliable, abundant and powerful source of energy, making wave energy converters a good addition to the current energy system. Even though wave energy is still a developing technology, it can be an alternative for the goal of a carbon-neutral energy mix, as it enables the generation of electrical energy in harbours, through integration into breakwaters, for example, which improves both the sustainability and energy independence of the harbour. Integrating a wave power plant into a breakwater brings benefits such as shared construction costs when the breakwater is not yet in place and easier access for construction, operation and maintenance. The integration of wave energy converters (WECs) into breakwaters has been most frequently achieved through the concept of Oscillating Water Column (OWC). This paper describes the design of a new Wells turbine for a breakwater-integrated OWC device. The strategy aims to optimise not only the efficiency of the turbine, but also the hydrodynamic and electrical efficiency, and thus, the efficiency of the device as a whole, as well as the reliability of the power-to-take-off system.